1970
DOI: 10.1590/s0034-89101970000200003
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento do Triatoma infestans sob várias condições de laboratório

Abstract: RESUMO: Foi observado o comportamento do T. infestans submetido às temperaturas de 25°C e 30°C, alimentado em galinha e camundongo e infectado pelo T. cruzi ou não. A temperatura mais elevada determinou um encurtamento da duração do ciclo evolutivo desde a eclosão do ôvo até a muda para a fase adulta, menores quantidades de sangue necessário para que se processasse a evolução, assim como menor número de repastos para obtenção do sangue. A alimentação com sangue de camundongo determinou um encurtamento no tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
9

Year Published

1973
1973
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 6 publications
(2 reference statements)
1
17
0
9
Order By: Relevance
“…However, it is possible to arrive to valid conclusions when methodologies and conditions are very similar. Some authors (Juarez 1970, Diotaiuti & Dias 1987, Lima-Gomes et al 1990, Braga et al 1998, Guarneri et al 2000a have published that the life cycle of at least seven Triatominae species were shorter on cohorts reared on mammals (mice) than on those reared on birds (chicken, pigeons or hens). However, the only two published researches about Meccus species (M. picturatus and M. longipennis), report no significant (p > 0.05) difference when cohorts fed on hens and fed on rabbits or fed on rats were compared (Martínez-Ibarra et al 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible to arrive to valid conclusions when methodologies and conditions are very similar. Some authors (Juarez 1970, Diotaiuti & Dias 1987, Lima-Gomes et al 1990, Braga et al 1998, Guarneri et al 2000a have published that the life cycle of at least seven Triatominae species were shorter on cohorts reared on mammals (mice) than on those reared on birds (chicken, pigeons or hens). However, the only two published researches about Meccus species (M. picturatus and M. longipennis), report no significant (p > 0.05) difference when cohorts fed on hens and fed on rabbits or fed on rats were compared (Martínez-Ibarra et al 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…Nas condições de temperatura e umidade relativa utilizadas em nosso experimento, observamos que número médio de ovos férteis por fêmea (50,4%) foi semelhante ao encontrado por Silva 14 (51,6%) em temperatura de 25 o C. Silva 14 observou ainda que o efeito da temperatura, acelera o processo embrionário em T. rubrovaria, dados iguais foram também encontrados por Juarez 6 para T. infestans e Juarez e Silva 7 para Triatoma sordida. Em nosso experimento a postura e o número de ovos férteis das 127 12 93 16 13 139 105 14 118 60 15 79 31 16 103 91 17 130 138 18 70 32 19 38 17 20 109 47 21 172 137 22 153 113 23 21 35 24 67 5 25 185 88 26 156 149 27 180 224 28 82 8 29 170 114 30 179 6 . Estudos sobre a viabilidade da colonização dos triatomíneos, em condições de laboratório são de interesse, mormente quando escasseiam exemplares do T. infestans, como vem acontecendo em nosso meio.…”
Section: Discussionunclassified
“…It is well established in the literature that food sources and environmental conditions may have influence on triatomine development (Juarez 1970, Gomes et al 1990, Guarneri et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Although triatomines can fed in a variety of hosts (mammalian, avian, reptilian and insects) in natural ecotopes, several studies carried out under laboratory conditions demonstrated that insects fed in mammals presented a shorter life cycle when compared with those fed on other blood sources (Juarez 1970, Guarneri et al 2000, Lorosa et al 2000.…”
mentioning
confidence: 99%